2015
DOI: 10.1007/s00299-015-1895-5
|View full text |Cite
|
Sign up to set email alerts
|

MsZEP, a novel zeaxanthin epoxidase gene from alfalfa (Medicago sativa), confers drought and salt tolerance in transgenic tobacco

Abstract: The zeaxanthin epoxidase gene ( MsZEP ) was cloned and characterized from alfalfa and validated for its function of tolerance toward drought and salt stresses by heterologous expression in Nicotiana tabacum. Zeaxanthin epoxidase (ZEP) plays important roles in plant response to various environment stresses due to its functions in ABA biosynthetic and the xanthophyll cycle. To understand the expression characteristics and the biological functions of ZEP in alfalfa (Medicago sativa), a novel gene, designated as M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…Under chilling-low irradiance stress, the expression levels of ClZE gradually decreased after 3 h of treatment, then were reduced rapidly and reached the minimal levels after 12 h of treatment (Figure 4(B)). These expression levels of ClZE were consistent with those previously reported in alfalfa homologue [27]. However, some studies indicate that the expression of ZE genes is not induced by light and low temperature, but by diurnal rhythm, as those characterized in tomato [20], Nicotiana [28] and Arabidopsis [29].…”
Section: Expression Of the Clze Gene Under Cold-low Irradiance Conditionsupporting
confidence: 91%
See 1 more Smart Citation
“…Under chilling-low irradiance stress, the expression levels of ClZE gradually decreased after 3 h of treatment, then were reduced rapidly and reached the minimal levels after 12 h of treatment (Figure 4(B)). These expression levels of ClZE were consistent with those previously reported in alfalfa homologue [27]. However, some studies indicate that the expression of ZE genes is not induced by light and low temperature, but by diurnal rhythm, as those characterized in tomato [20], Nicotiana [28] and Arabidopsis [29].…”
Section: Expression Of the Clze Gene Under Cold-low Irradiance Conditionsupporting
confidence: 91%
“…Reduction of thermal dissipation in transgenic lines can lead to increase of the excitation pressure, and ultimately cause damage of the photosynthetic apparatus [20]. Since Fv/Fm represents the maximum potential of PSII quantum efficiency and is used as a parameter for measurement of the function of PSII reaction centres, the decrease in Fv/Fm mainly reflects the characteristics of photoinhibition [27].…”
Section: Effects Of Chilling-low Light Treatment On Npq and Fv/fm Of mentioning
confidence: 99%
“…The SbpAPX gene confers salinity and drought tolerance to tobacco plants at different developmental stages5. Similarly, the overexpression of the novel gene(s) LcSAIN1, MsZEP and the TF, Zmhdz10 in plants leads to the improved tolerance to oxidative stress that is caused by drought and salt stresses161733.…”
Section: Discussionmentioning
confidence: 99%
“…Global transcript profiling has revealed that many genes are co-ordinately regulated by salt and drought stress1415. A novel MsZEP gene was cloned from alfalfa for functional validation by heterologous expression in tobacco, and the gene confers drought and salt tolerance in transgenic plants16. The overexpression of a novel Zmhdz10 in rice and Arabidopsis led to a significantly improved tolerance to oxidative stress caused by drought and salt stresses17.…”
mentioning
confidence: 99%
“…However, it is challenging to identify key genes in the stress tolerance mechanism. A number of novel genes have been characterized, such as SbUSP, SbSDR1, MsZEP , and IbZFP1 , but other novel or uncharacterized genes may play a critical role in stress tolerance (Singh et al, 2016; Udawat et al, 2016; Wang et al, 2016; Zhang et al, 2016). The EST database contains about 30% novel or uncharacterized clone sequences for Salicornia .…”
Section: Introductionmentioning
confidence: 99%